Specific Nutrient Intake Via Diet and/or Supplementation in Relation to Female Stress: A Cross-Sectional Study - Delia McCabe; Jana Bednarz; Craig Lockwood; Timothy H. Barker (Mary Ann Liebert, 2020)
Background: Women are negatively impacted by psychological stress and despite the prolific use of dietary supplements to manage stress there is little evidence to support their use for such. This study examined the relationship between intake of specific nutrients through diet and/or dietary supplementation and level of perceived stress. Method: In this cross-sectional study of adult Australian women (n?=?74), perceived stress was measured using the Perceived Stress Scale, dietary intake was assessed using a validated Food Frequency Questionnaire, and supplement usage was recorded using a Supplement Use Questionnaire. Results: Potentially substantive reductions in stress scores were associated with polyunsaturated fatty acid supplementation: ?-linolenic acid (mean difference [MD]?=??3.34, 95% confidence interval [CI]?=??7.97 to 1.29), linoleic acid (MD?=??4.08, 95% CI?=??8.97 to 0.82), ?-linolenic acid (MD?=??2.23, 95% CI?=??7.20 to 2.74), and eicosapentaenoic acid (EPA)/docosahexaenoic acid (DHA) (MD?=??4.05, 95% CI?=??8.07 to ?0.03). There were negative correlations between intake of vitamin B6 and vitamin C and stress (??=??0.50 and ?0.35, respectively). Compared with nonsupplementers, stress scores were on average 0.92 units lower among those supplementing with magnesium and vitamin B6 concurrently (95% CI?=??3.88 to 2.03). An increase in vitamin B6 through food was related to lower stress scores. For most nutrients, intake from food was positively associated with supplementation status. Conclusion: There is some evidence to suggest potentially meaningful associations between intake of particular nutrients and stress, although CIs were wide and there were no statistically significant relationships observed. Further research is warranted to investigate any potential benefits more precisely using randomized controlled trials or large-scale observational studies.